DIFFERENCE OF ENERGY BALANCE IN PADDY FIELD, SUKHOTHAI PROVINCE - Pukngam, Somnimirt; Boonyawat, Samakkee (วารสารวนศาสตร์ไทย, 2022)
Study on difference of energy balance was carried out in paddy field, Sukhothai province by using data recorded by Automatic Weather Station (AWS) during 1997-1998. The objective is to indicate the difference of energy balance in the paddy field both in the planting season and dry season. It was found that latent heat in planting season was about 10.9 MJ m-2 day-1 or 75.1 percent of net radiation which higher than sensible heat (1.8 MJ m-² day-1 or 12.4 percent of net radiation). The heat storage in soil and water was about 0.3 and 1.6 MJ m-2 day-1 or 1.8 and 10.8 percent of net radiation respectively. In dry season, after rice harvesting, or dry season the sensible heat was higher than latent heat particularly from January to May and March to April. The sensible heat was about 7.7 MJ m-2 day-1 or 64.9 percent of net radiation while latent heat was about 3.0 MJ m-2 day-1 or only 25.2 percent of net radiation. The heat storage in soil in dry season after harvesting period was about 1.2 MJ m-2 day-1 or 9.9 percent of net radiation. The main factor in the difference of energy balance was water submerged in paddy field.